BUSINESS INTELLIGENCE (BI) PRESIDENTIAL CANDIDATES BASED ON SOCIAL NETWORK ANALYSIS (SNA) WITH TWITTER DATA - Ali, Ichsan; Girsang, Abba Suganda (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Tadulako, 2024)
The twitter social network is widely used to discuss all kinds of topics, including those related to politics. Analyzing online conversations on Twitter to map the popularity of political figures as candidates for the Indonesian presidential election is a popular and challenging research area. In the Twitter network, citizens can express themselves and communicate with political figures. The conversational data in Twitter is very complex, so Business Intelligence is needed to transform raw data into meaningful and useful information to see the popularity of Indonesian presidential election candidates. The analysis used is Social Network Analysis (SNA) by measuring Degree Centrality, Eigenvector Centrality, Betweenness Centrality, Closeness Centrality. The presidential candidates in this study, Ganjar Pranowo with a twitter account â€œganjarpranowoâ€, Puan Maharani with a twitter account â€œpuanmaharani_riâ€, and Anies Baswedan with a twitter account â€œaniesbaswedanâ€. The actor